2012
DOI: 10.1128/jb.00648-12
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis PrgJ, a VirB4-Like ATPase, Mediates pCF10 Conjugative Transfer through Substrate Binding

Abstract: The Enterococcus faecalis prg and pcf genes of plasmid pCF10 encode a type IV secretion system (T4SS) required for conjugative transfer. PrgJ is a member of the VirB4 family of ATPases that are universally associated with T4SSs. Here, we report that purified PrgJ dimers displayed ATP binding and hydrolysis activities. A PrgJ nucleoside triphosphate (NTP) binding site mutation (K471E) slightly diminished ATP binding but abolished ATP hydrolysis in vitro and blocked pCF10 transfer in vivo. As shown with affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 46 publications
7
60
0
Order By: Relevance
“…Finally, once PcfC binds the pCF10 substrate, the receptor delivers its cargo to the VirB4-like PrgJ ATPase, possibly for further processing prior to translocation (50). Soluble PcfC⌬N103 binds PrgJ in vitro (50), prompting us to test whether AAD PcfC or NBD/ CTD PcfC participates in PrgJ binding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, once PcfC binds the pCF10 substrate, the receptor delivers its cargo to the VirB4-like PrgJ ATPase, possibly for further processing prior to translocation (50). Soluble PcfC⌬N103 binds PrgJ in vitro (50), prompting us to test whether AAD PcfC or NBD/ CTD PcfC participates in PrgJ binding.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble PcfC⌬N103 binds PrgJ in vitro (50), prompting us to test whether AAD PcfC or NBD/ CTD PcfC participates in PrgJ binding. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, VirB11 may function with VirB4 to coordinate a structural change in VirB2 pilin protein and mediate VirB2 binding to other T4SS components, which in turn affects pilus polymerization (Kerr and Christie, 2010). Accumulating genetic studies and recent structural studies support a model in which VirB4 dimers or homomultimers contribute both structural information for the assembly of a trans-envelope channel competent for DNA transfer and an ATP-dependent activity for configuring this channel as a dedicated export machine (Fronzes et al, 2009a;Durand et al, 2010Durand et al, , 2011Kerr and Christie, 2010;Li et al, 2012;Pena et al, 2012;Wallden et al, 2012). In addition, the TrIP assay results showed that translocating DNA substrates first interact with the VirD4 receptor, followed by VirB11 ATPase, suggesting VirB11 may function together with VirB4 and deliver the T-DNA substrate to the transfer channel of the T4SS (Cascales and Christie, 2004a;Bhatty et al, 2013;Chandran, 2013;Christie et al, 2014).…”
Section: Transport Of T-dna and Virulence Proteins Via Type IV Secretmentioning
confidence: 99%